The experiences of children and their parents in paediatric diabetes services should inform the development of communication skills for healthcare staff (the DEPICTED Study). - Hawthorne, K; Bennert, K; Lowes, L; Channon, S; Robling, M; Gregory, J (2011)
AIMS: The aims of this study were to describe users' experience of paediatric diabetes services to inform development of an intervention to improve communication between staff and patients in secondary care within a wider study (the DEPICTED Study). METHODS: Methods adapted for paediatric settings were used to set up six audio-recorded focus discussion groups with a total of 32 participants. Transcriptions and notes were coded thematically (supported by NVivo software) and analytic themes developed with discussion between researchers. RESULTS: Three main themes developed: the lack of two-way conversation about glycaemic control in clinic settings; the restricting experience of living with diabetes; and the difficult interactions around diabetes the children had with their schools. Doctors in particular were seen as struggling to link these themes of everyday life in their consultations with children and their parents. Children felt marginalized in clinics, despite active involvement in their own blood glucose management at home. CONCLUSIONS: Health professionals need to balance a requirement for good glycaemic control with realism and appreciation of their patients' efforts. There is a need for a systematic approach to consulting, in particular using agenda setting to ensure that the issues of both the patient and the professional are addressed. A framework for a conceptual approach is discussed. How a patient is involved is as important as what is communicated during a consultation.